Validating Subsurface Monitoring as an Alternative Option to Surface M&V - The CO2CRC's Otway Stage 3 Injection. (July 2017) - Jenkins, Charles; Marshall, Steve; Dance, Tess; Ennis-King, Jonathan; Glubokovskikh, Stanislav; Gurevich, Boris; La Force, Tara; Paterson, Lincoln; Pevzner, Roman; Tenthorey, Eric; Watson, Max
Abstract: Future CO2 storage projects will require Monitoring and Verification (M&V) operations at the CO2 storage site to understand the behavior of the CO2 plume, including the assurance that leakage of the CO2 has not occurred. Current surface based monitoring technologies may be unable to yield sufficient resolution or accuracy. CO2CRC, in conjunction with its Australian partners, is developing the Otway Stage 3 Project to identify and validate sub-surface monitoring techniques and configurations as a key element of a risk-based M&V program in large scale CCS projects. Subsurface monitoring approaches will be tested on a plume of CO2 from an array of monitoring wells. Primary monitoring methods will be pressure tomography and downhole seismic, although other modalities (gravity, electromagnetic) are also being considered.